Study on Mercury Methylation in the Amazonian Rivers in Flooded Areas for Hydroelectric Use - Gomes, Vinicius M. (2019)
This study aimed to estimate in laboratory the temporal production of methylmercury during the filling of reservoirs of hydropower plants and to correlate it to the ecosystem of different locations in northern Brazil: Jirau hydropower plant in the Madeira River in the state of Rondônia (white waters—under construction), Cana Brava hydropower plant in the Tocantins River in the state of Goiás (clear waters—completed), and the Negro River in the Amazon (black waters—comparative). After collecting water, soil, and sediment samples in the regions mentioned, a microcosm was created to reproduce the conditions close to those found in nature. Water/soil/Hg0/Hg2+ and water/sediment/Hg0/Hg2+ were added to glass recipients. Next, methylmercury concentration was monitored by atomic fluorescence spectrometry, total organic carbon by TOC 5000A, and physical and chemical parameters such as pH, redox potential, and dissolved oxygen, for 25 days. The results obtained allow concluding that organic matter plays an important role, providing excess methyl groups to react with inorganic Hg and form organic Hg. The Negro River, which has higher contents of organic matter in its soil, water, and sediment, presented higher potential of mercury methylation in both experiments performed, followed by rivers Madeira and Tocantins.